Patient perspectives on the barriers associated with medication adherence to oral chemotherapy. (March 2018) - Muluneh, Benyam; Deal, Allison; Alexander, Maurice D; Keisler, Meredith D; Markey, Janell M; Neal, Jennifer M; Bernard, Stephen; Valgus, John; Dressler, Lynn G
Purpose: Appropriate use of oral chemotherapy is a challenge for patients and clinicians. The purpose of this study was to analyze cancer patients' use of oral chemotherapies and identify opportunities to improve adherence. Methods: We developed a 30-question survey to address frequency and reasons for reducing/skipping doses; sources of information for oral chemotherapy use; perceived importance of food–drug effects; and ease of understanding labeling directions. Results: Ninety-three patients taking oral chemotherapies with chronic myeloid leukemia, renal cell carcinoma, breast cancer, and colorectal cancer completed the survey. This was a well-educated population with 69% (n = 62) having completed some college; 51% (n = 47) female and 59% (n = 54) older than 50 years of age. Thirty percent of patients reported forgetting to take their oral chemotherapy at least "sometimes". Younger patients (<50 vs. ≥50, p = 0.002), shorter treatment duration (<6 vs. ≥6 months p = 0.03), or with chronic myeloid leukemia (vs. other diagnoses, p = 0.015) forget to take their oral chemotherapy at higher rates. Twenty-three percent (n = 21) indicated they intentionally skipped their oral chemotherapies and 38% (n = 8) of those did not inform their physicians. Forty-one percent (n = 28) taking drugs with significant food–drug effects did not think about their last meal before taking their oral chemotherapy and 80% (n = 55) did not understand the potential interactions. Additionally, 39% (n = 36/92) never looked at labeling and 15% (n = 14/91) had difficulty understanding label directions. Conclusion: There are three main barriers associated with appropriate use of oral chemotherapies: misunderstanding about the timing of drug with food; stopping drug without informing physicians; and difficulty understanding labeling directions. A multipronged approach is needed to optimize communication of directions for optimal oral chemotherapy use.